The first government of Evo Morales and the MAS in Bolivia: Notes on the relationship with Peru (1990-2009) - Rojas Samanez, Fernando (2023)
The electoral victory in 2005 of Evo Morales and his political party, the Movement for Socialism (MAS) in Bolivia, marked the culmination of a years-long process of political mobilization and organization. This originated in the departments of La Paz, Oruro, and Cochabamba, led by indigenous social sectors in the Andean region of the country, associated with leftist organizations. The electoral process unfolded within the framework of conventional democracy with active citizen participation. It signified a departure from the political regimes of so-called “traditional” parties and the assumption of government by a popular, socio-cultural, and fundamentally indigenous movement. This movement aimed to transform the country’s socio-economic structure, adopting an anti-liberal and markedly nationalist stance, ultimately striving to establish a Plurinational State. President Evo Morales, a historic leader of coca leaf producers and an active trade unionist, played a crucial role that extended far beyond Bolivia, projecting influence into the regional context, particularly in neighboring Andean Peru.